The design and usability testing of DACADE: a tool supporting systematic data collection and analysis for design students - S. Abd. Aziz, Madihah; Lindgaard, Gitte; Whitfield, T.W. Allan (Springer Berlin Heidelberg, 2013)
Norman claims that designers are bereft of statistical knowledge to perform effectively [10], stating that designers must understand technology, business and psychology to support design decisions. For designers to acquire the necessary statistical skills, design curricula should incorporate statistical courses teaching systematic data collection and data analysis. This paper presents the development and formative usability tests of the prototypes of a software tool called DACADE intended to support design students collecting and analyzing data systematically early in the design phase. It uses a 2D map and a Napping® technique to support effective and efficient communication between designers and target audiences in the design decision process by providing visual data and descriptive statistics without needing statistical knowledge.